Interaction of the nanobio-based reagent with sodium fluorescein and lipids via bioinformatics for forensic fingerprint visualisations - Lin, Khor Tze; Mahat, Naji Arafat; Azman, Aida Rasyidah; Abdul Wahab, Roswanira; Oyewusi, Habeebat Adekilekun; Abdul Hamid, Azzmer Azzar (Taylor & Francis, 2023)
Being commonly found at crime scenes, fingerprints are crucial for human identification, attributable to their uniqueness, persistence and systematic classification of ridge patterns. In addition to latent fingerprints being invisible to the naked eye, the escalating trends of disposing forensic evidence bearing such prints in watery bodies would further complicate criminal investigations. Taking into account the toxicity of small particle reagent (SPR) commonly used in visualising latent fingerprints on wet and non-porous objects, a greener alternative using the nanobio-based reagent (NBR) has been suggested. However, NBR only applies to white and/or relatively light-coloured objects. Thus, conjugation of sodium fluorescein dye with NBR (f-NBR) may be beneficial for increasing the contrast of fingerprint on multi-colored objects. Hence, this study was aimed at investigating the possibility of such conjugation (i.e., f-NBR) as well as proposing suitable interactions between the f-NBR and lipid constituents of fingerprints (tetra-, hexa- and octadecanoic acids) via molecular docking and molecular dynamics simulations. The binding energies between CRL with its ligands were observed at 8.1, 5.0, 4.9 and 3.6 kcal/mole for sodium fluorescein, tetra-, hexa- and octadecanoic acids, respectively. Besides, the formations of hydrogen bonds observed in all complexes (ranged between 2.6 and 3.4 Å), further supported by the stabilized root mean square deviation (RMSDs) plots in MD simulations. In short, the conjugation of f-NBR was computationally feasible, and thereby merits further investigations in the laboratory